2015
DOI: 10.1111/pcmr.12392
|View full text |Cite
|
Sign up to set email alerts
|

RAC1 P29S regulates PD‐L1 expression in melanoma

Abstract: Summary Whole exome sequencing of cutaneous melanoma has led to the detection of P29 mutations in RAC1 in 5–9% of samples, but the role of RAC1 P29 mutations in melanoma biology remains unclear. Using reverse phase protein array analysis to examine the changes in protein/phospho-protein expression, we identified cyclin B1, PD-L1, Ets-1, and Syk as being selectively upregulated with RAC1 P29S expression and downregulated with RAC1 P29S depletion. Using the melanoma patient samples in TCGA, we found PD-L1 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 39 publications
0
64
0
1
Order By: Relevance
“…Rac1 overexpression has been found in various types of cancer, such as lung cancer, gastric cancer, pancreatic cancer, bladder cancer and breast cancer 43, 44, 45, 46, 47. Moreover, activation of Rac1 can increase cancer cell migration, adhesion, invasion, proliferation and metastasis 40, 44, 48, 49, 50. In our previous study, we found that miR‐124 repressed osteosarcoma cell proliferation, migration and invasion by targeting Rac1 expression 34.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 overexpression has been found in various types of cancer, such as lung cancer, gastric cancer, pancreatic cancer, bladder cancer and breast cancer 43, 44, 45, 46, 47. Moreover, activation of Rac1 can increase cancer cell migration, adhesion, invasion, proliferation and metastasis 40, 44, 48, 49, 50. In our previous study, we found that miR‐124 repressed osteosarcoma cell proliferation, migration and invasion by targeting Rac1 expression 34.…”
Section: Discussionmentioning
confidence: 99%
“…This mutation confers resistance to Raf and MEK inhibitors, thus having significant clinical therapeutic significance (20). Interestingly, expression of Rac1 P29S in melanoma patients correlates with PD-L1 up-regulation, thus potentially contributing to suppression of an anti-tumor immune response (21). These findings could also be extended to other cancers since the Rac1 P29S hotspot mutation has been identified in head and neck, and endometrial cancers (22).…”
Section: Emerging Paradigms In Rho Gtpase Hyperactivation In Cancermentioning
confidence: 99%
“…In addition to the potential role for Rac1 in the control of PD-L1 expression and suppression of anti-tumor immune responses described above (21), it is becoming increasingly evident that Rac1 is involved in acquired resistance. Ectopic expression of Rac1 GEFs, Rac1 activators such as BCAR3/AND-34, or constitutively active Rac1, promotes resistance to anti-estrogens, a widely used endocrine therapeutic approach for estrogen receptor-positive (ER+) breast cancer patients (57,58).…”
Section: Targeting Rac Gtpases: Can We Overcome Therapy Resistance?mentioning
confidence: 99%
“…The Rac-GEF DOCK1 has recently been demonstrated as a critical regulator of the malignant phenotypes induced by Rac1 P29S (41). From a pharmacological standpoint, the Rac1 P29S mutation is associated with resistance to Raf inhibitors and PD-L1 up-regulation, thus contributing to evading immune surveillance and potentially serving as a predictive biomarker for therapy resistance in melanoma (42, 43). A recent interesting study revealed that Rac1 mutant melanoma cells are highly sensitive to Pak inhibition, a result consistent with the augmented engagement of Rac effectors by the Rac1 P29S mutant (44).…”
Section: Aberrant Rac Expression and Activity In Human Cancermentioning
confidence: 99%
“…As indicated above, Rac1 P29S mutated melanoma cells are resistant to clinical BRAF inhibitors but highly sensitive to Pak inhibition (42, 44), and they exhibit elevated expression of PD-L1, a ligand of the checkpoint protein PD-1 that plays a fundamental role in immune evasion (43). Conceivably, pharmacological inhibition of Rac could be beneficial in combination with anti-PD-L1 monoclonal antibodies or other immune checkpoint inhibitors.…”
Section: Concluding Remarks - Rac and Tumor Susceptibility: From Biocmentioning
confidence: 99%